Students’ perceptions on the change from in-person to remote course along COVID-19 outbreak: a case study for General Chemistry - Novaki, Luzia Peres (2021)
The course of General Chemistry is part of the mandatory curriculum to be taken by undergraduates to obtain a Bachelor's degree in Science and Technology at the Federal University of ABC. During the course, face-to-face classes are planned, but due to the COVID-19 pandemic scenario, in 2020 the course was initially taught in person, and later adapted to remote mode. After the end of the classes, students reported their perceptions by filling out a questionnaire related to accessibility to remote mode, perceptions of theoretical classes and laboratories, learning, self-assessment and an overview of the course, focusing on the change that occurred when to the offer modality. As for the theoretical classes, the results indicated that perceptions do not seem to have been altered by the change from face-to-face to remote mode. On the other hand, according to their perceptions, remote laboratories did not allow the development of essential cognitive and practical skills. Despite these limitations, the overall results showed a positive perception of the course, allowing the course to be completed satisfactorily. These results can constitute subsidies and precautions to be considered for future planning of disciplines in a hybrid way, especially regarding the limitations inherent to the remote mode.